The Impact of the USMCA Trade Agreement on the U.S.-Mexico Border Security Cooperation - Kim, Ahyeon (Eximia, 2024)
The United States-Mexico-Canada Agreement (USMCA) replaced its predecessor, the North American Free Trade Agreement (NAFTA), and has provided crucial updates to make the agreement relevant to the 21st century. Developing the connection between the two bordering nations and increasing security without sacrificing trade benefits allowed for additional developments in information-sharing systems, cyber security, and AI for threat detection. This paper aims to explore the impact of the updated agreement as well as its potential future implications and ramifications.